Parkes Weber syndrome in a child - David Ortiz Limonta; Ana Gómez Jurado; Sandra A. Sánchez Figueredo (Centro Provincial de Información de Ciencias Médicas, 2016)
The case report of a 4 years child is described assisted initially in the Pediatrics Service of the Social Security Ecuadorian Institute Hospital of Ibarra in Ecuador Republic and then in the Vascular Surgery Service, where she was diagnosed Parkes Weber syndrome.